TOURIST INDUSTRY OF UKRAINE IN THE CONTEXT OF MODERN INTEGRATION PROCESSES - Rodina, O.G. (The actual problems of regional economy development, 2021)
Article is devoted to the research of the tourism industry of Ukraine in the context of modern integration processes. In today's world, tourism is a catalyst for the social and economic development of the country, has a great influence on such key areas as trade, transport, communications, construction and many others. For many countries around the world, tourism is an essential tool, and often functions as a source of income in the country's economy, an effective tool for creating a favorable investment climate and a positive image of the state. The preconditions of Ukraine for effective development of inbound and domestic tourism have been generalized: favorable climate, advantageous geographical position and relief, rich natural, tourist and recreational and cultural-historical potential. A SWOT analysis of the development of Ukrainian tourism is presented, which allows us to conclude that Ukraine objectively has tourism potential and opportunities for its development, but at the moment it is not used effectively by the country. The competitive advantages of the tourism industry of Ukraine are analyzed, detailed analysis of this industry is carried out. It makes sense that increasing the competitiveness of the tourism sector should become the key tasks of the modern Ukrainian economy. It is important to focus on creating an attractive image of Ukraine in the international market as a country that can provide tourists not only with access to cultural and natural sites, but also security, comfortable living and travel conditions, balanced pricing policy, high standards of hospitality. At the same time, there is a need to constantly work on improving their own tourism product and its competitiveness. The impact of the pandemic on the development of tourism is considered and the need to organize and develop all tourist destinations and resources, which will contribute to the further social and economic development of both external and domestic tourism. It is substantiated that taking certain measures to overcome the pandemic and further improve the market economy in all areas of activity, including tourism, is necessary.